MtNF-YA1, A Central Transcriptional Regulator of Symbiotic Nodule Development, Is Also a Determinant of Medicago truncatula Susceptibility toward a Root Pathogen - Rey, Thomas; Laporte, Philippe; Bonhomme, Maxime; Jardinaud, Marie-Françoise; Huguet, Stéphanie; Balzergue, Sandrine; Dumas, Bernard; Niebel, Andreas; Jacquet, Christophe (Frontiers in Plant Science, 2016)
Plant NF-Y transcription factors control a wide array of biological functions enabling appropriate reproductive and developmental processes as well as adaptation to various abiotic and biotic environments. In Medicago truncatula, MtNF-YA1 was previously identified as a key determinant for nodule development and establishment of rhizobial symbiosis. Here we highlight a new role for this protein in compatibility to Aphanomyces euteiches, a root pathogenic oomycete. The Mtnf-ya1-1 mutant plants showed better survival rate, reduced symptoms, and increased development of their root apparatus as compared to their wild type background A17. MtNF-YA-1 was specifically up-regulated by A. euteiches in F83005.5, a highly susceptible natural accession of M. truncatula while transcript level remained stable in A17, which is partially resistant. The role of MtNF-YA1 in F83005.5 susceptibility was further documented by reducing MtNF-YA1 expression either by overexpression of the miR169q, a microRNA targeting MtNF-YA1, or by RNAi approaches leading to a strong enhancement in the resistance of this susceptible line. Comparative analysis of the transcriptome of wild type and Mtnf-ya1-1 led to the identification of 1509 differentially expressed genes. Among those, almost 36 defence-related genes were constitutively expressed in Mtnf-ya1-1, while 20 genes linked to hormonal pathways were repressed. In summary, we revealed an unexpected dual role for this symbiotic transcription factor as a key player in the compatibility mechanisms to a pathogen.